Comparison of complications in very obese women undergoing hysterectomy – Abdominal vs laparoscopic approach with short- and long-term follow-up. (September 2022) - Sehnal, Borek; Klat, Jaroslav; Herboltova, Petra; Hanacek, Jiri; Fanta, Michael; Valha, Petr; Hruda, Martin; Vasicka, Ian; Halaska, Michael J.
Abstract: Background: Surgical treatment of obese female patients represents a real challenge. Over the last decade, minimally invasive techniques for hysterectomy have emerged. These approaches reduce the invasiveness of standard surgical procedures while maintaining efficacy and feasibility. Objective: To evaluate the rates of perioperative, early, mid-term and late postoperative complications in very obese [body mass index (BMI) ≥ 35 and < 40 kg/m 2 ] and severely obese (BMI ≥ 40 kg/m 2 ) women who underwent total (non-radical) hysterectomy. Design: A prospective comparative multi-centre non-randomized study. Methods: In total, 328 consecutive total (non-radical) hysterectomies were performed at seven teaching gynaecological centres. Of these, 153 (46.6%) were performed using an open laparotomy (LT) approach and 175 (53.4%) were performed laparoscopically (LS). All data were collected by medical specialists at the pre-operative examination prior to surgery, during surgery and three times postoperatively (during hospital stay, at 6-week follow-up and 6 months following surgery). Another analysis considered a total of 206 women who underwent laparoscopic hysterectomy. The subjects were divided according to BMI into 120 very obese women (BMI ≥ 35 and < 40 kg/m 2 ) and 86 severely obese women (BMI ≥ 40 kg/m 2 ). Results: The total number of composite perioperative complications was significantly lower in the LS group ( p  = 0.006). Composite complications occurred significantly more often in patients in the LT group compared with the LS group in the early ( p  < 0.001) and mid-term ( p  < 0.001) postoperative periods. In the late postoperative period, the total number of composite postoperative complications did not differ significantly between the groups ( p  < 0.396). Among 206 patients who underwent laparoscopic hysterectomy, the number of complications was generally low; the rates of composite perioperative ( p  = 0.393), early ( p  = 0.642), mid-term ( p  = 0.738) and late ( p  = 1) postoperative complications were generally low; and frequency did not differ significantly with BMI. Conclusion: The LS approach does not increase intra-operative morbidity associated with surgery, and has significantly better outcomes in terms of the postoperative complication rate.